Computational fluid dynamics analysis of the effect of simulated plaques in the left coronary artery: A preliminary study. - Chaichana, T.; Jewkes, James; Sun, Zhonghua (Modelling and Simulation Society of Australia and New Zealand, 2011)
Background: Atherosclerosis is the most common cause of coronary artery disease which is formed by plaque presence inside the artery wall leading to blockage of the blood supply to the heart muscle. The mechanism of atherosclerotic development is dependent on the blood flow variations in the artery wall during cardiac cycles. Characterization of plaque components and investigation of the plaques with subsequent coronary artery stenosis and myocardial dysfunction has been extensively studied in the literature. However, little is known about the effect of plaques on hemodynamic changes to the coronary artery, to the best of our knowledge. Investigation of the position of plaques in the coronary artery and its corresponding regional hemodynamic effects will provide valuable information for prediction of the coronary artery disease progression. The aim of this study is to investigate the effect of simulated plaques in the left coronary artery using computational fluid dynamics. Methods: A left coronary artery model was generated based on a computed tomography data in a patient suspected of coronary artery disease. The model consists of the left main coronary artery, left anterior descending and left circumflex, together with side branches. Simulated coronary plaques were created and placed in the left main coronary artery and left anterior descending with a resultant lumen stenosis of more than 50%. The blood rheology and pulsatile velocity at the left coronary artery were applied to simulate the realistic physiological situation. A transient simulation was performed to demonstrate the hemodynamic changes during cardiac phases. The flow velocity pattern, wall shear stress and wall pressure were measured at peak systolic and middle diastolic phases in the models with and without presence of plaques.Results: Our results showed that the flow change due to the simulated coronary plaques demonstrated a large circulation region at the left coronary bifurcation, and the velocity through bifurcation was increased. In contrast, a smooth flow pattern was observed in the non-calcified regions and flow velocity was low at the bifurcation. Low wall pressure was present in the coronary artery with a simulated coronary plaque whereas there was high wall pressure in the normal coronary artery. The simulated plaques resulted in high wall shear stress when compared to the low wall shear stress present in the normal coronary artery. The simulated coronary plaques interfered with blood flow behavior which was demonstrated as a large region of disturbed flow at coronary bifurcation. Conclusion: We successfully simulated the coronary plaques in a realistic coronary model and the effect of plaques in different locations on subsequent hemodynamic changes. Our preliminary study is useful for further investigation of the development of atherosclerosis in patients with different cardiac risk factors.